UPAYA MEMASARKAN PITUTOUR TRANSWISATA DALAM RANGKA MENARIK MINAT WISATAWAN - , HISYOM PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesian tourism problems are numerous, ranging themselves economically and socially. Economically, tourism is a great avenue. Source of funding is derived from the government budget and foreign place tourism itself. Service company is needed in the service of the travelers to travel services, one of which is Pitutour Transwisata engaged in services that are in Wonogiri. In this case to find out the products offered, how to market constraints Pitutour Transwisata and know what possessed Pitutour Transwisata. This research was conducted with several data collection methods were interviews, observations (observation), literature. Interviews were conducted by a question and answer directly to the respondent. From the data that have been obtained are then processed in the writing of this final. Pitutour Transwisata is a travel agency that is relatively new so it is necessary to introduce marketing to tourists. Something new to market is not easy. In marketing existing products Pitutour Transwisata make a brochure and fanspage. The author makes a SWOT analysis and SWOT matrix which results to promote its products.